2012
DOI: 10.1111/j.1945-1474.2011.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Perinatal Safety Initiative to Reduce Adverse Obstetric Events

Abstract: A comprehensive perinatal safety initiative (PSI) was incrementally introduced from August 2007 to July 2009 at a large tertiary medical center to reduce adverse obstetrical outcomes. The PSI introduced: (1) evidence-based protocols, (2) formalized team training with emphasis on communication, (3) standardization of electronic fetal monitoring with required documentation of competence, (4) a high-risk obstetrical emergency simulation program, and (5) dissemination of an integrated educational program among all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…Three studies reported on the decrease of birth trauma after training, one unspecified [60] and two on brachial plexus injury [34,44]. An abstract on an Americanised PROMPT study not included in our review also reported significant reductions in brachial plexus injuries and perinatal HIE [80].…”
Section: Impact Of Skill Training In Emergency Obstetric and Neonatalmentioning
confidence: 96%
See 2 more Smart Citations
“…Three studies reported on the decrease of birth trauma after training, one unspecified [60] and two on brachial plexus injury [34,44]. An abstract on an Americanised PROMPT study not included in our review also reported significant reductions in brachial plexus injuries and perinatal HIE [80].…”
Section: Impact Of Skill Training In Emergency Obstetric and Neonatalmentioning
confidence: 96%
“…Thirteen studies had been conducted in [19][20][21][22][23][24][25][26][27][28] 6 DH (L2&L3) -HIC 10 RCT 2a,b,c 3b NHS Foundation Trust, Liverpool, UK [44,45] --HIC 1 Before-after 4b,c Victoria, Australia [46] 7 [48] --LMIC 1 Before-after 1 2b −−− −−− Sub-Saharan Africa (7 countries) [49] --LMIC 1 Before-after 1 2b,c −−− −−− Somaliland, Somalia [50] 3 8 LMIC 1 Before-after 1 2b,c 3a 4b Making it Happen, Bangladesh & India [52] 4 DH (Bangl.) [54] 3 DH; 3 FH 40 LMIC 1 Quasi-experimental 3c CRM based National study, US [58] 15 -HIC 1 RCT 4c Beth Israel Deaconness Medical Center, US [59] 1 TTH -HIC 1 Before-after 2a 4b,c Perinatal Safety Initiative, US [60] 1 TH -HIC 1 Before-after 3a 4b,c Rhode Island Hospital, US [61] 1 -HIC 1 Before-after 4b,c Geneva University Hospital, Switzerland [63] 1 TTH -HIC 1 Before-after 1 2a 3a TeamSTEPPS, US [18] 3 CH -HIC 1 RCT 2a 4c OBCTT, Southeast US [62] 1 TTH -HIC 1 Quasi-experimental before-after 1 2a,b,c −−− −−− OTHER CEmONC, Tanzania [17] 1 DH LMIC 1 Before-after 3c Copenhagen University Hospital, Denmark [64] 1 TTH -HIC 1 Before-after 1 2a,b 3a 4b University of Oporto, Portugal [65] 1 TTH -HIC 1 Before-after 1 2b 3a * In progress -abstracts not included [31,32] DH = district hospital L1 = level 1 −−− = studies not going beyond Kirkpatrick level 2 RH = referral hospital L2 = level 2 (secondary/regional) FH = field hospital TH = tertiary hospital/medical centre L3 = level 3 (tertiary) CH = community hospital TTH = tertiary and teaching hospital included in the studies spans the whole spectrum from tertiary teaching hospitals to community-and field hospitals. Three LMIC studies included community health centres.…”
Section: Synopsis Of Peer-reviewed Articles Included In the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was possible to interpret guidelines for patient risk assessment [33], to improve PS multicomponent safety initiatives in the healthcare system [35] [39], enhance approaches to communication [38], share experiences by debriefing [40], team training [41], standardized documentation [42] and analysis of claim files to identify opportunities for improvement [44]. In summary, the perspectives of patients [33] Table 2.…”
Section: Evidence Related To Key Components Of Long Andmentioning
confidence: 99%
“…Convergent validity of the scale scores was measured by correlations with external teamwork related items [34]. The study by Wagner et al [35] used logistic regression. In summary, the most common weaknesses of the included studies related to design, sampling and analysis.…”
Section: Summary Of Quality Assessmentmentioning
confidence: 99%